2012
DOI: 10.1103/physrevlett.108.225502
|View full text |Cite
|
Sign up to set email alerts
|

Damage-Cluster Distributions and Size Effect on Strength in Compressive Failure

Abstract: We investigate compressive failure of heterogeneous materials on the basis of a continuous progressive damage model. The model explicitely accounts for tensile and shear local damage and reproduces the main features of compressive failure of brittle materials like rocks or ice. We show that the size distribution of damage-clusters, as well as the evolution of an order parameter, the size of the largest damage-cluster, argue for a critical interpretation of fracture. The compressive failure strength follows a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 25 publications
10
44
0
Order By: Relevance
“…Typically, only a very small proportion of the microcracks revealed by destructive thin sectioning after the test result in detectable acoustic emissions [11]. As a consequence, experimental data provide only limited insight into the complexity of the microscopic processes at work prior to failure, notably the probability distributions of the relevant parameters, their scaling properties, and their population dynamics.Theoretical approaches to the dynamics and statistics of rupture cascades have typically been based on stochastic fracture models comprising lattices of springs [12], beams [13,14], fuses [15,16], or fibers [17][18][19]. However, such lattice models involve a strong simplification of the material microstructure and the inhomogeneous stress field.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, only a very small proportion of the microcracks revealed by destructive thin sectioning after the test result in detectable acoustic emissions [11]. As a consequence, experimental data provide only limited insight into the complexity of the microscopic processes at work prior to failure, notably the probability distributions of the relevant parameters, their scaling properties, and their population dynamics.Theoretical approaches to the dynamics and statistics of rupture cascades have typically been based on stochastic fracture models comprising lattices of springs [12], beams [13,14], fuses [15,16], or fibers [17][18][19]. However, such lattice models involve a strong simplification of the material microstructure and the inhomogeneous stress field.…”
mentioning
confidence: 99%
“…Theoretical approaches to the dynamics and statistics of rupture cascades have typically been based on stochastic fracture models comprising lattices of springs [12], beams [13,14], fuses [15,16], or fibers [17][18][19]. However, such lattice models involve a strong simplification of the material microstructure and the inhomogeneous stress field.…”
mentioning
confidence: 99%
“…A power-law distribution of crack sizes was also observed with a scalar spring model, and it was reported that the distribution was exponential for the low-strain loadings and approaches to a power law as the loading increases [36]. Girard et al [12] saw an identical trend of the damage cluster size distribution for their finite-element model, applying a random distribution of disorder. In their case, the size distribution of the damage clusters follows a power law with an exponential cutoff at the peak load under compressive loading.…”
Section: Damage Clustersmentioning
confidence: 87%
“…The exponent obtained for the fiber bundle models is 1.86 [38], while scalar spring models yield τ = 2 [36]. Progressive damage finite-element models under the compressive loading give different exponents with different levels of heterogeneity as the reported values range from 2.6 to 3.6 [12]. It is known that the percolation theory calculates the Fisher's exponent in two dimensions as τ 2D = 187/91 ≈ 2.05 and τ 3D = 2.18 in three dimensions [17].…”
Section: Damage Clustersmentioning
confidence: 93%
See 1 more Smart Citation